Birds of isolated small forests in Uganda - Dranzoa, Christine; Williams, Charlie; Pomeroy, Derek (Journal of East African Ornithology, 2011)
This study concerns birds recorded from four small forests in Uganda, three of them being naturally isolated and the fourth being a fragment of the once extensive forests of southern Uganda. Whilst the forest interior birds in the natural forest islands might be considered subsets of those found in larger forests, the fact that the species composition in the three naturally isolated patches are almost completely different from each other, and in one case appear to have changed with time, suggests a major element of chance in which species occur where. There is also a strong indication of species turnover amongst the forest interior birds in these forests. The fact that, together and over time these small forests supported 37 forest interior species, suggests that, collectively, small forests (of which there are many in Uganda) do have conservation value. The evidence of species turnover with time, if confirmed, would increase the numbers of species involved and implies that even interior species do sometimes travel significant distances across other habitats.
Keywords: Birds; Small forests